introducing the Heidelberg approach to conflict research - Trinn, Christoph; Wencker, Thomas (European political science, 2018)
Many conflict-data projects are based on narrow or disjointed concepts of political conflict. They either cover only limited segments of reality or put distinct but related forms of conflict phenomena in conceptual ‘bins’ rather than integrating them into a more comprehensive concept. In addition, conflict intensity is frequently measured by only one indicator, the number of fatalities, which represents only part of the consequences and none of the means of violent conflict. Means and consequences, taken together, constitute the intensity of a conflict. They ought to be combined to arrive at a valid measurement. The Heidelberg approach to conflict research addresses both issues, offering a broad yet differentiated and integrative concept of conflict and a multi-dimensional and multi-indicator approach to intensity. This improves our abilities to recognise and classify conflictive phenomena; to capture conflict-transformation; and to arrive at a valid measurement of intensity. The approach is applied in the new DISCON dataset, comprising data on 155 violent and non-violent interstate, intra-state, and substate conflicts in Asia and Oceania from 2000 to 2014, disaggregated into more than 6300 region-month intensities.
published online 15 December 2016
Gesehen am 31.01.2019